Precise Distance and Velocity Measurement for Real Time Locating Using a Frequency Modulated Continuous Wave Secondary Radar Approach - Röhr, Sven; Gulden, Peter; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2008)
We present a frequency-modulated continuous-wave secondary radar concept to estimate the offset in time and in frequency of two wireless units and to measure their distance relative to each other. By evaluating the Doppler frequency shift of the radar signals, the relative velocity of the mobile units is measured as well. The distance can be measured with a standard deviation as low as 1 cm. However, especially in indoor environments, the accuracy of the system can be degraded by multipath transmissions. Therefore, we show an extension of the algorithm to cope with multipath propagation. We also present the hardware setup of the measurement system. The system is tested in various environments. The results prove the excellent performance and outstanding reliability of the algorithms presented.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.LEH.precis